Descripción de la transformación digital de la información financiera y su efecto en el ejercicio de profesión contable de los egresados de la universidad Antonio Nariño Sede Tunja (2023)
The objective of this research is to identify the main effects of the digital transformation of financial information in the exercise of the accounting profession in the graduates of the Antonio Nariño University, Tunja headquarters, mainly the four periods of the of accounting that are empirical period, period of genesis and appearance of double entry, classical period and finally the period of scientific evolution, through its history, the importance of each of the periods was analyzed and explained, it is mentioned the currents where the theories used to generate financial information are established